PENGARUH AUDIT OPERASIONAL DAN TATA KELOLA KEUANGAN TERHADAP OPTIMALISASI GROSS PROFIT MARGIN DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI PADA INDUSTRI KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Wiluk Lianawati (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2025)
The The growth of the construction industry is experiencing a trend that tends to decline from year to year. This study aims to determine the influence of operational audit and financial governance with the audit committee as a moderation variable on gross profit margin optimization. The research method used is descriptive verification using a quantitative approach by collecting secondary data in the form of financial statements and annual reports of construction companies obtained from the Indonesia Stock Exchange in 2020-2022 with the population being construction industry companies, while the number of samples in this study is 10 companies that meet the sample criteria during the research period with sampling techniques using purposive sampling method. Data analysis method and hypothesis test using the logistic regression method and Moderated Regression Analysis (MRA) with the support of the SPSS Version 27 program. The results showed that that operational audit and financial governance have a significant influence on the optimization of gross profit margin. And the results of the research for the moderation variables of the audit committee were simultaneously able to moderate the operational audit to the optimization of gross profit margin, but the audit committee was not able to moderate the financial governance variables to the optimization of gross profit margin.